A first peek at firms' cash flow dynamics in the pandemic year - Oblak, Ana (Economic and business review, 2021)
Using a comprehensive database of financial data and data on public support, we aim at documenting the actual (and not predicted) effects of the Covid-19 pandemic on firms’ liquidity. A drain of the non-financial corporations’ liquidity was unprecedented and highly asymmetric across sectors. A simple descriptive analysis enables us to evaluate (partially) the effectiveness of support measures and to provide insights on how well-targeted support measures were from the sectoral perspective. Acting in concert, the governments and the European Union (EU) institutions concerned seem to succeed in preventing massive illiquidity (for now). Crisis measures were targeted mostly at firms with positive cash flow in the pre-pandemic year and ensured additional 3.4 percent of firms from the analysed sectors to sustain positive cash flow and 0.6 percent of firms to recover. Strikingly, the share of inactive firms decreased in 2020 compared to 2019, which might indicate that measures supported de facto dead companies. Considering the proportion of firms, the most vulnerable sector benefited most, but not when we think about a reduction in cash flow compensated for with direct grants. The approach “whatever is necessary” in a form of “flat” public support might thus lead to not optimally targeted beneficiaries.
Keywords: administrativni ukrepi; cash flows; government regulation; pandemic; pandemija